US Withdrawal from Afghanistan: Its Political Impacts on Pakistan - Noreen, Ghazala; Junaid, Tahir (The Lighthouse Journal of Social Sciences, 2022)
The withdrawal of US forces from Afghanistan has significant political impacts on Pakistan, given the country's close proximity. The study has highlighted the impacts like increased in terrorism and extremist activities in both Afghanistan and Pakistan, as the Taliban and other extremist groups have filled the vacuum left by the departure of US forces. Hence, this led to destabilization of the region, with unfavorable political effects on Pakistan. The study aims to highlight far-reaching political impacts on Pakistan of withdrawal of US forces from Afghanistan. The research is purely qualitative and secondary sources are used to collect data. The study's methodology is entirely qualitative, relying on secondary sources to collect data. The US withdrawal also presents an opportunity for Pakistan to play a more constructive role in the region, working with other nations to promote stability in the area and prevent the resurgence of extremism in Afghanistan. Achieving this would necessitate the Pakistani government taking a more proactive and collaborative approach towards its neighbor, as well as collaborating with other nations and international organizations to address the underlying drivers of conflict in the region. It is critical for the government to carefully consider its response to promote stability, enhance trade ties, and prevent the spread of extremist violence. The data was analyzed using thematic analysis and a coding method.